The Effect of Instructive Program Using the Video on Alluding Skill in Basket-Ball for Secondary Students - djamel, mokrani (Journal of Physical Education Health and Sport, 2018)
The research aimed to know the effect of using the video in instructive lessons to ameliorate the alluding skill level for secondary students (16 – 17) years in Mostaganem – Algeria. The researchers used the practical way by using previous and later exam on a design of 24 students separated on two groups once is practical and other is exactive in scholar season 2014/2015. The exams used presented in exams measure practice in alluding skill in basket-ball (alluding from stability, from jumping and alluding from step). After statistic traitment of the results, the researcher found that; The instructive program by using the video affected in amelioration of alluding skill in basket-ball for secondary students. The practical design dominates on instructive program using the video on exactive design counted on traditional way in alluding skill results in basket-ball.